Highly Efficient Dual-Band Rectifier Based on Symmetric Impedance Control Network - Eojin Kim; Yeonsoo Kim; Juntaek Oh (IEEE Access)
This study proposes a dual-band rectifier that utilizes a symmetric impedance control network (SICN) for highly efficient wireless power transfer. The proposed rectifier comprises a voltage doubler and an SICN connected to each diode of the voltage doubler. The SICN controls the input impedance seen by each diode at two fundamental frequencies and the second harmonic impedance at those frequencies at the diode terminals, thus controlling the voltage across each diode. This minimizes the overlap time when the two diodes are turned on and maximizes the voltage applied to them. Thus, the maximum power conversion efficiency (PCE) is achieved within a wide input power range at the two frequencies. The proposed rectifier is designed and fabricated with a compact size of $28.9× 38.9$ mm2. Measurements show that the maximum PCE reaches 82.1 % and 75 % at 0.915 and 2.42 GHz, respectively. Moreover, the PCE remains above 50% over a wide input power range of 6.8–30.5 dBm at 0.915 GHz and 14.8–31 dBm at 2.42 GHz. The PCE exceeds 50% at bandwidths of 0.79–1.66 GHz and 2.3–2.53 GHz at an input power of 24.5 dBm.